2022
DOI: 10.1108/ijsms-08-2021-0172
|View full text |Cite
|
Sign up to set email alerts
|

Reversing equity transfer in sponsorship for competitive advantage of emerging local events: quantitative evidence from an experimental study

Abstract: PurposeBuilt upon the balance theory and schema theory, this study examined the impact of sponsors' intangible attributes, including consumer-based brand equity (CBBE) and brand-event image fit (BEIF), on consumer responses to emerging local events (ELEs), as well as major boundary conditions of this mechanism.Design/methodology/approachTheoretical hypotheses were tested using multivariate analysis of covariance and structural equation modeling with the data from two experiments: the experiment in the pilot st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Namely, Chen et al [25] stated that corporate image is a crucial component to increase customers' trustworthiness for creating potential corporate profitability, particularly in times of crisis. Also, Wang et al [26] showed that corporate image can be the most critical factor in increasing the public's perception and identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Namely, Chen et al [25] stated that corporate image is a crucial component to increase customers' trustworthiness for creating potential corporate profitability, particularly in times of crisis. Also, Wang et al [26] showed that corporate image can be the most critical factor in increasing the public's perception and identification.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have confirmed that sponsorship can promote CI. For example, Wang et al [26] argued that sponsorship events can alter individuals' perceived event value and further increase the public's perception and identification to the image of the sponsors. Rajabi et al [27] demonstrated that different sponsorship-fit profiles influence respondents' attitudes toward sponsors, especially in enhancing the visibility and credibility of the sponsors.…”
Section: Corporate Image (Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived quality is explained as how the consumer perceives the brand's quality, compared to its actual performance (Zeithaml, 1988). According to Wang et al . (2022, p. 750), “this intangible feeling is more attached to consumers' active affection rather than passive perception.” On the other hand, brand loyalty, according to Aaker (1991), is the attachment that consumers have to a brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a marketing angle, many applied schema theoretic papers are framed from a promotion, product, or brand recall perception and cognition perspective [45,46]. This paper applies schema theory from a different context.…”
Section: The Empirical Literaturementioning
confidence: 99%